2018
DOI: 10.1111/idj.12351
|View full text |Cite
|
Sign up to set email alerts
|

Effect of body weight and behavioural factors on caries severity in Mexican rural and urban adolescents

Abstract: Overweight was not associated with caries severity in the overall population, but it became a statistically significant risk indicator in adolescents living in the rural area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 25 publications
1
28
0
3
Order By: Relevance
“…Such detailed information aids in the management of the patient's dental health and decision‐making regarding selection of the appropriate treatment methods . Our results showed no difference in the maximum ICDAS code recorded per child between the NW and OW groups ( P > .05), corroborating the results from a similar study on Mexican adolescent subjects . The NW group, however, showed a higher prevalence of extensive carious lesions (ICDAS 5‐6) and the OW group exhibited a higher prevalence of initial carious lesions (ICDAS 1‐2).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Such detailed information aids in the management of the patient's dental health and decision‐making regarding selection of the appropriate treatment methods . Our results showed no difference in the maximum ICDAS code recorded per child between the NW and OW groups ( P > .05), corroborating the results from a similar study on Mexican adolescent subjects . The NW group, however, showed a higher prevalence of extensive carious lesions (ICDAS 5‐6) and the OW group exhibited a higher prevalence of initial carious lesions (ICDAS 1‐2).…”
Section: Discussionsupporting
confidence: 88%
“…Studies using the DMF index in Germany and Iran have shown a positive association between dental caries and obesity in children aged 6‐11 years . Conversely, studies using WHO criteria or ICDAS demonstrated no association between obesity and caries in children/adolescents aged 6‐12 years. Differences in methodology, such as experimental design, population and sample size, socioeconomic status, gender, educational level, occupation of the parents, lifestyle, dental caries index, BMI classification, physical activity, dietary habits, use of fluoride and oral hygiene, should be considered in attempting to explain the conflicting data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An ad hoc questionnaire was build-up to assess general health, eating habits, oral hygiene and the self-perception of oral conditions, based on previous surveys [12][13][14][15]. Direct face to face interviews were conducted with at least one parent of the children under the age of 12, while older children were asked to answer a self-administered questionnaire.…”
Section: Methodsmentioning
confidence: 99%